Why osteoarthritis of the knee is called “a wound that does not heal” and why Tai Chi is an effective treatment - Huston, Patricia (Frontiers in Medicine, 2023)
Osteoarthritis (OA) of the knee is common and is often described as a "wound that does not heal" and first line therapy includes aerobic exercise, strength training and normalization of weight. Tai chi is an aerobic, mind-body practice that is specifically recommended for OA of the knee. This review addressed two questions: Why does the local immune response get dysregulated in OA of the knee? And why is tai chi so effective? These questions can now be answered due to a better understanding of what causes OA of the knee at the cellular level. OA begins with tissue damage that causes a phenotypic shift in synovial macrophages and the release inflammatory cytokines. This is the first phase of the normal healing and repair process. Cytokines stimulate cytokine release in cells of the cartilage, bone and surrounding tissues. When tissue damage is repetitive, however, there is repetitive release of inflammatory cytokines, and the normal healing process stops. This is made worse when there is systemic low-grade inflammation and other exacerbating factors. Tai chi improves alignment, optimizes the biomechanical forces on the knee, decreases systemic inflammation and stabilizes the knee joint. This creates the conditions for the normal healing and repair process to resume. It is possible any aerobic activity that does not place adverse forces on the knee will have a similar effect. Further research is indicated.